Forecasting stock market volatility with macroeconomic variables in real time - Jörg Döpke; Daniel Hartmann; Christian Pierdzioch (Deutsche Bundesbank, 2006)
We compared forecasts of stock market volatility based on real-time and revised macroeconomic data. To this end, we used a new dataset on monthly real-time macroeconomic variables for Germany. The dataset covers the period 1994-2005. We used a statistical, a utility-based, and an options-based criterion to evaluate volatility forecasts. Our main result is that the statistical and economic value of volatility forecasts based on real-time data is comparable to the value of forecasts based on revised macroeconomic data.
Keywords: G11; E44; C53; 330; Forecasting stock market volatility; Real-time macroeconomic data; Evaluation of forecasting accuracy; Börsenkurs; Volatilität; Prognoseverfahren; Aktienmarkt; Konjunktur; Makroökonomischer Einfluß; Schätzung; Deutschland